The chapman-type rearrangement in pseudosaccharins: the case of 3-(methoxy)-1,2-benzisothiazole 1,1-dioxide - Kaczor, A. (2014)
The thermal Chapman-type rearrangement of the pseudosaccharin 3-(methoxy)-1,2-benzisothiazole 1,1-dioxide (MBID) into 2-methyl-1,2-benzisothiazol-3(2H)-one 1,1-dioxide (MBIOD) was investigated on the basis of computational models and knowledge of the structure of the reactant and product in the isolated and solid phases. X-ray diffraction was used to obtain the structure of the substrate in the crystalline phase, providing fundamental structural data for the development of the theoretical models used to investigate the reaction mechanism in the condensed phase. The intra- and different intermolecular mechanisms were compared on energetic grounds, based on the various developed theoretical models of the rearrangement reactions. The energetic preference (ca. 3.2 kJ mol 1, B3LYP/6-31+G(d,p)) of interover intramolecular transfer of the methyl group is predicted for the ‘‘quasi-simultaneous” transfer of the methyl groups model, explaining the potential of MBID towards [1,30]-isomerization to MBIOD in the condensed phases. The predicted lower energy of MBIOD relative to MBID (ca. 60 kJ mol 1), due to the lower steric hindrance in the MBIOD molecule, acts as a molecular motor for the observed thermal rearrangement.